Effect of different hydrolysis time and enzymes on chemical properties, antioxidant and antihyperglycemic activities of edible bird nest hydrolysate - Alia Syafieqah Zulkifli,; Abdul Salam Babji,; Lim, Seng Joe; Arnida Hani Teh,; Norlida Mat Daud,; Hafeedza Abdul Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Edible bird nest (EBN) is a dried glutinous secretion from the salivary glands of swiftlet species commonly found in the Southeast Asian region, including Malaysia. It is consumed traditionally by the Chinese as food delicacy and also considered as an important ingredient in traditional Chinese medicine for its beneficial health effects. The aim of this study was to evaluate the effect of enzymatic hydrolysis using alcalase, papain and papaya juice hydrolyze at 0.5 to 3 hr on the degree of hydrolysis (DH), protein solubility, concentration of reducing sugar, antioxidant and anti-hyperglycemic activity. In general, an increase in hydrolysis time increases the DH and soluble protein digestion rate. However, the concentration of reducing sugar was not affected by hydrolysis time. The solubility of proteins was highest for alcalase and papain at 3 h, while papaya juice at 2 h. Papain showed the highest antioxidant activity in 1 and 2 h of hydrolysis time whereas at 3 h, results for both papain and alcalase were higher compared to papaya juice. Result of anti-hyperglycemic activity showed that only EBN hydrolyzed using papaya juice has positive activity. Based on this study, enzymatic hydrolysis had improved the functional properties of EBN and results showed the potential of EBN to be developed as natural antioxidants and anti-hyperglycemic agents.